Mapping the terrain: a scoping review of empirical studies on the big five personality traits and QoL in China - Chen, Cuiren (Frontiers in Psychology, 2024)
The relationship between personality traits and Quality of Life (QoL) (QoL) has garnered increasing scholarly attention, particularly within the context of China. This scoping review synthesizes existing literature on the connection between the Big Five personality traits and QoL among the Chinese population. The review explores correlations, measurement instruments, and theoretical frameworks employed in these studies. This review addresses three primary research questions: (1) How do the Big Five personality traits correlate with QoL in different Chinese subpopulations, and what are the mediating or moderating factors? (2) What instruments assess these traits and QoL in the Chinese cultural context, and how are they validated? (3) What theoretical or disciplinary frameworks guide this research in China?Following a systematic PRISMA-ScR framework and a customized "C-BFQLC" protocol, the study identified 170 relevant documents. After rigorous screening, ten studies met the inclusion criteria, constituting 5.03% of the initial records. This scoping review critically examines the interplay between the Big Five personality traits and QoL in China, a context marked by rapid socioeconomic changes and cultural diversity. Employing a systematic approach guided by the PRISMA-ScR framework and our unique 'C-BFQLC' protocol, we meticulously analyzed 170 documents, selecting nine that met our rigorous inclusion criteria. Despite the emerging nature of this research area in the Chinese context, our study reveals significant insights into how individual personality traits influence various dimensions of well-being. The implications of these findings are profound, extending beyond academic discourse to inform healthcare policies, organizational behavior, and social welfare programs in China. Our review not only offers a comprehensive synthesis of the current research landscape but also identifies critical gaps in the literature. It emphasizes the urgent need for further culturally nuanced research to understand the complex dynamics of personality traits and QoL in China. This work lays a foundational framework for future investigations and the development of tailored interventions aimed at enhancing the well-being of diverse Chinese populations, including the elderly, people with disabilities, and specific occupational groups.